On the Uses of LP and NLP to Formulate Game Theory Problems: A Brief Review - Zaman, Muhammad Adib Uz; Rabiei Hosseinabad, Emad (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Game theory has been used for many years when making important strategical decisions. Many phenomena, specially in social and behavioural sciences are being modelled using game theory concepts. Game theory has seen its successful implementation in socio economic and political decision making. From its beginning back in early 1920s, game theoretical models have been developed and used to explain many real-life scenarios. John Von Neumann formally introduced game theory during world war II back in 1944 along with fellow researcher Oskar Morgenstern. Since then, game theory has evolved in its own pace. In parallel, linear (LP) and nonlinear programming (NLP) have been crucial in many important research directions involving real life problems. The objective of this article is to review some published papers in literature that present many uses of LP and NLP formulation in game theoretical fields to aid in important strategic decisions.